ANALYZING THE ROLE OF TRANSNATIONAL ORGANIZED CRIME IN TRAFFICKING IN PERSONS IN INDONESIA: A CASE STUDY ON MIDDLE EAST ILLEGAL MIGRATION ROUTES - Atsil Syah Gibran; M Fadly Khusairy (Polteknik Imigrasi, 2023)
This study analyzes the role of transnational organized crime in human trafficking in Indonesia, especially in illegal immigration routes in the Middle East. The case studies conducted in this study will provide a clear picture of the modus operandi, perpetrators and victims of human trafficking incidents involving transnational criminal networks. Efforts to prevent and combat human trafficking in Indonesia can be implemented through a variety of strategies, including public awareness-raising, enforce rigorous prosecution of perpetrators, strengthen international cooperation, and provide victims with adequate protection and rehabilitation. However, many challenges remain, including lack of coordination.